ANTIFUNGAL, CYTOTOXIC AND PHYTOTOXICITY OF AERIAL PART OF RANUNCULUS MURICATUS - Aslam, Muhammad Shahzad; Rehman, Rubina; Choudhary, Bashir A.; Ijaz, Abdul Subhan; Uzair, Muhammad; Ahmad, Muhammad Syarhabil (Universal Journal of Pharmaceutical Research, 2016)
Objectives: The present research is preliminary biological screening of aerial plant of Ranunculus muricatus (Ranunculaceae). Dichloromethane and methanol extracts of the aerial plant were investigated for their antifungal, phytotoxic and cytotoxic activities. Methods: Anti-fungal, cytotoxicity and phytotoxicity activities were performed by agar tube dilution assay, brine shrimp lethality bioassay and lemna bioassay respectively. Dichloromethane and methanolic extracts exhibited significant phytotoxicity against Lemna minor having Paraquat as standard drug and incubation condition (28±1ºC). Results: None of extracts presented any significant cytotoxic activity having Imipenum and Etoposide as standard drug respectively. Both extract had non-significant antifungal activity but it has been noted that methanol extract showed 30% inhibition with linear growth at 70 mm, when compared with control; only against Microsporum canis. Ranunculus muricatus showed significant phytotoxicity. Conclusion: The phytotoxicty assay is a valuable major screen for weedicide investigation. Additionally, modern studies are currently carried out to identify the allelopathic constituents by isolation, purification and structure elucidation to find out as effective herbicidal. Peer Review History: Article received on- 7 August; Revised 11 September; Accepted 9 October; Available online 15 November 2016 Academic Editor: Dr. Ali Abdullah Al-yahawi , Al-Razi university, Department of Pharmacy, Yemen, alyahawipharm@yahoo.com Reviewer(s) detail: Dr. Awofisayo, O Abosede , University of Uyo, Nigeria, shalomgirl08@yahoo.com Prof. Dr. Ali Gamal Ahmed Al-kaf , Sana'a university, Yemen, alialkaf21@gmail.com